2020
DOI: 10.20944/preprints202008.0515.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effectiveness of the Government Subsidies on the Photovoltaic Industry--Spatial Econometric Analysis Based on China’s Provincial Panel Data(2011-2018)

Abstract: Energy resources are important sources of social and economic development, human survival and security. However, energy resources are objective and scarce, especially the fossil energy, such as coal, oil, natural gas, etc. Human survival environment is increasingly damaged, and the condition of energy is also gradually becoming deficient, so it is necessary to develop new energy resources to meet the increasing demand of material civilization. Solar energy can meet the needs of human development in the future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…Additionally, Wang Yuzhen [2] investigated whether China's rare earth policy achieved the expected outcomes. Studies by Shao Min et al [3] indicated that excessive government subsidies tend to restrain firms' productivity. Furthermore, Feng Haihong et al [4] argued that tax incentives positively stimulate firms' R&D investments.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Wang Yuzhen [2] investigated whether China's rare earth policy achieved the expected outcomes. Studies by Shao Min et al [3] indicated that excessive government subsidies tend to restrain firms' productivity. Furthermore, Feng Haihong et al [4] argued that tax incentives positively stimulate firms' R&D investments.…”
Section: Introductionmentioning
confidence: 99%